gp130 cytokines are positive signals triggering changes in gene expression and axon outgrowth in peripheral neurons following injury - Zigmond, Richard (Frontiers in Molecular Neuroscience, 2012)
Adult peripheral neurons, in contrast to adult central neurons, are capable of regeneration after axonal damage. Much attention has focused on the changes that accompany this regeneration in two places, the distal nerve segment (where phagocytosis of axonal debris, changes in the surface properties of Schwann cells, and induction of growth factors and cytokines occur) and the neuronal cell body (where dramatic changes in cell morphology and gene expression occur). The changes in the axotomized cell body are often referred to as the “cell body response.” The focus of the current review is a family of cytokines, the glycoprotein 130 (gp130) cytokines, which produce their actions through a common gp130 signaling receptor and which function as injury signals for axotomized peripheral neurons, triggering changes in gene expression and in neurite outgrowth. These cytokines play important roles in the responses of sympathetic, sensory, and motor neurons to injury. The best studied of these cytokines in this context are leukemia inhibitory factor (LIF) and interleukin (IL)-6, but experiments with conditional gp130 knockout animals suggest that other members of this family, not yet determined, are also involved. The primary gp130 signaling pathway shown to be involved is the activation of Janus kinase (JAK) and the transcription factors Signal Transducers and Activators of Transcription (STAT), though other downstream pathways such as mitogen-activated protein kinase (MAPK)/extracellular signal-regulated kinase (ERK) may also play a role. gp130 signaling may involve paracrine, retrograde, and autocrine actions of these cytokines. Recent studies suggest that manipulation of this cytokine system can also stimulate regeneration by injured central neurons.